2002
DOI: 10.1046/j.1529-8027.2002.02025.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuralgic amyotrophy: variable expression in 40 patients

Abstract: This study looks at disease diversity, location of lesions, and progression of neuralgic amyotrophy (NA). Forty patients (28 male and 12 female, age range 15 to 70 years) were clinically examined. Muscle atrophy, weakness, and sensory impairment were assessed. Needle EMG and conduction velocities were performed. Careful clinical, electrophysiological, laboratory, and radiological studies excluded other illness. Twenty-two patients were followed for 2 years. Antecedent fever and upper-respiratory tract infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 32 publications
3
54
0
5
Order By: Relevance
“…Those that have provided data suggest a mononeuropathy multiplex. 3,18 In this case, there was no electromyographic evidence of spontaneous paraspinal activity confirming the clinical impression that radiculopathy was unlikely. For this patient, nerve conduction studies and electromyography categorized the lesion to a likely combined mononeuropathy and plexopathy as opposed to a plexopathy alone or mononeuropathy.…”
Section: Discussionsupporting
confidence: 65%
“…Those that have provided data suggest a mononeuropathy multiplex. 3,18 In this case, there was no electromyographic evidence of spontaneous paraspinal activity confirming the clinical impression that radiculopathy was unlikely. For this patient, nerve conduction studies and electromyography categorized the lesion to a likely combined mononeuropathy and plexopathy as opposed to a plexopathy alone or mononeuropathy.…”
Section: Discussionsupporting
confidence: 65%
“…In 2002, Cruz-Martínez et al reported 40 patients with NA (28 males and 12 females, age: 15-70 years) and described that the overall prognosis of NA is good in general, despite the severity and extent of the lesions. In follow-up studies in 22 of 40 patients (43 affected nerves), the muscles innervated by 41 of 43 (95.3%) nerves reached good function within the 2-year follow-up period (7).…”
Section: Discussionmentioning
confidence: 90%
“…Except for the classical presentation of NA, there are some phenotypic variations including involvement of nerves outside the brachial plexus (cranial nerves, phrenic nerve, or lumbosacral plexus), mononeuropathic form, bilateral symptoms, prominent sensory symptoms, or painless attack (17). For instance, Cruz-Martínez reported 7 bilateral impairment, 4 accessory nerve, 4 facial nerve, and 1 phrenic nerve involvement in the above-mentioned report (7). Moreover, the severity of an episode can vary hugely between patients, and even between different attacks in the same patient (17).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Use of corticosteroids reduces the time until the start of paresis recovery but does not improve longterm outcome 19,22) . Most patients will generally have good recovery after 2-3 years with supportive management 3,19,20) . We managed all patients conservatively by initiating early physiotherapy, analgesics, and/or steroids, and the pain and motor weakness of all 10 patients improved significantly.…”
Section: Discussionmentioning
confidence: 99%